P PRAKTIK PEMBIAYAAN PRODUK CICIL EMAS MENGGUNAKAN AKAD MURABAHAH DALAM PERSPEKTIF HUKUM EKONOMI SYARI’AH (Studi Kasus di Bank Syariah Indonesia Kantor Cabang Cempaka Mas Jombang): GOLD PRODUCT FINANCING PRACTICES USING MURABAHAH AGREEMENTS IN SYARI'AH ECONOMIC LEGAL PERSPECTIVE (Case Study at Bank Syariah Indonesia Cempaka Mas Jombang Branch Office) - Nur Azizah; Syai'in; Pratanto Rahayu, Wedi (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2025)
Banking is currently developing a lot, especially banking with sharia principles, this is to avoid elements of usury, gharar, haram and wrongdoing. Bank Syariah Indonesia is here by selling Gold Installment Financing products with the practice of murabahah contracts. Murabahah is the sale and purchase of goods at the original price with additional agreed profits. The aim of this research is to; 1) analyze the practice of financing gold installments using a murabahah contract at Bank Syariah Indonesia Cempaka Mas Jombang Branch Office. Second, to find out the perspective of sharia economic law on the practice of financing gold installment products using a murabahah contract at Bank Syariah Indonesia, Cempaka Mas Jombang Branch Office. The method used is a qualitative research method, which uses a conceptual approach and a phenomenological approach. Data collection from this research used observation techniques, interviews, documentation and library data. The results of this research are that in the practice of financing gold installments at Bank Syariah Indonesia Cempaka Mas Jombang Branch Office using a murabahah contract, there are four elements; 1) parties involved in gold installment financing, 2) object of financing, 3) agreement/contract